Factors affecting stem cell mobilization in patients treated with hematopoietic peripheral stem cell transplantation [Periferik hematopoietik kök hücre nakli yapılan hastalarda kök hücre mobilizasyonunu etkileyen faktörler] - (:unkn) unknown (Marmara University, 2011)
Objectives: To assess the factors affecting stem cell mobilization in patients treated with hematopoietic peripheral stem cell transplantation. Patients and Methods: Autologous bone marrow transplants in 143 patients with 169 stem cell harvesting procedures were analysed retrospectively. Results: Stem cell mobilization was done with Filgrastim in 89 patients (52.7%) and with Lenograstim in 80 patients (47.3%). For stem cell harvesting, Fresenius apheresis device was used in 69 patients (40.8%), while Haemonetics apheresis device was used in 100 patients (59.2%). In univariate analysis, patient's diagnosis (p=0.005), number of treatment lines before the apheresis procedure (p=0.0004), number of leukocytes and CD34+ cell count at the first day of the apheresis procedure (p=0.0001 and p=0.0005, respectively), mobilization with filgrastim (p=0.00004) and mobilization with the Fresenius apheresis device (p=0.007) were statistically significant. In multivariate analysis, diagnosis of the patient (p=0.01), mobilization with filgrastim (p= 0.001), mobilization with Fresenius apheresis device (p=0.03), and leukocyte count at first day of apheresis (p=0.006) were important factors affecting peripheral stem cell mobilization. Conclusion: Patient's diagnosis, mobilization with filgrastim and Fresenius apheresis device, peripheral blood leukocyte count at the first day of apheresis seem to be important in affecting peripheral stem cell mobilization.
Keywords: Apheresis; Filgrastim; Hematopoietic peripheral stem cell transplantation; Lenograstim; Stem cell mobilization